Five-year monitoring of a gay-friendly voluntary counselling and testing facility in Switzerland: who got tested and why? - Gumy Cédric (BMC Public Health, 2012)
Abstract Background An increase in new HIV cases among men who have sex with men (MSM) has been reported in Switzerland since 2001. A rapid result HIV testing for MSM through voluntary counselling and testing (VCT) facility (“Checkpoint”) was opened in Geneva in 2005. This gay-friendly facility, the first to open in Switzerland, provides testing for sexually transmitted infections (STI) and rapid result HIV testing and counselling. Our objective was to analyze Checkpoint’s activity over its first five years of activity and its ability to attract at-risk MSM. Methods We used routine data collected anonymously about the facility activity (number of clients, number of tests, and test results) and about the characteristics of the clientele (sociodemographic data, sexual risk behaviour, and reasons for testing) from 2005 to 2009. Results The yearly number of HIV tests performed increased from 249 in 2005 to 561 in 2009. The annual proportion of positive tests among tests performed varied between 2% and 3%. Among MSM clients, the median annual number of anal intercourse (AI) partners was three. Roughly 30% of all MSM clients had at least one unprotected anal intercourse (UAI) experience in the previous 12 months with a partner of different/unknown HIV status. The main reason for testing in 2007, 2008, and 2009 was “sexual risk exposure” (~40%), followed by “routine” testing (~30%) and “condom stopping in the beginning of a new steady relationship” (~10%). Clients who came to the facility after a sexual risk exposure, compared to clients who came for "routine testing" or "condom stopping" reasons, had the highest number of AI partners in the previous 12 months, were more likely to have had UAI with a partner of different/unknown HIV status in the previous 12 months (respectively 57.3%, 12.5%, 23.5%), more likely to have had an STI diagnosed in the past (41.6%, 32.2%, 22.9%), and more likely to report recent feelings of sadness or depression (42.6%; 32.8%, 18.5%). Conclusion Many of Checkpoint's clients reported elevated sexual risk exposure and risk factors, and the annual proportion of new HIV cases in the facility is stable. This VCT facility attracts the intended population and appears to be a useful tool contributing to the fight against the HIV epidemic among MSM in Switzerland.